The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0100-879x2001000600018
|View full text |Cite
|
Sign up to set email alerts
|

Central injection of captopril inhibits the blood pressure response to intracerebroventricular choline

Abstract: In the present study, we investigated the involvement of the brain renin-angiotensin system in the effects of central cholinergic stimulation on blood pressure in conscious, freely moving normotensive rats. In the first step, we determined the effects of intracerebroventricular (icv) choline (50, 100 and 150 µg) on blood pressure. Choline increased blood pressure in a dose-dependent manner. In order to investigate the effects of brain renin-angiotensin system blockade on blood pressure increase induced by chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The dose of choline used in this study was chosen based on reports in the literature that demonstrated that the pressor response induced by ICV choline is dose-dependent and that the highest documented dose (150 μg) immediately increases MABP, catecholamines, and AVP (20,24). The MABP response to 150 μg choline is sustained for approximately 15 minutes as shown by our preliminary studies as well as studies in the literature (36). Only animals that had a positive response to angiotensin II-induced polydipsia, reflecting accurate placement of the cannula in the lateral ventricle, were used in these studies.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The dose of choline used in this study was chosen based on reports in the literature that demonstrated that the pressor response induced by ICV choline is dose-dependent and that the highest documented dose (150 μg) immediately increases MABP, catecholamines, and AVP (20,24). The MABP response to 150 μg choline is sustained for approximately 15 minutes as shown by our preliminary studies as well as studies in the literature (36). Only animals that had a positive response to angiotensin II-induced polydipsia, reflecting accurate placement of the cannula in the lateral ventricle, were used in these studies.…”
Section: Methodssupporting
confidence: 75%
“…Reports in the literature suggest that the observed effects are mediated via central nicotinic receptors (35). In addition, the brain renin-angiotensin system may be involved in the pressor response elicited by ICV choline because ICV pretreatment with captopril, an angiotensin converting enzyme inhibitor, has been shown to inhibit the pressor response induced by ICV choline (36). …”
Section: Discussionmentioning
confidence: 99%
“…However, studies by IsbilBuyukcoskun et al demonstrated that captopril given i.c.v. blocked choline-induced pressor effect in conscious rats [8].…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, central choline administration enhances plasma catecholamine and vasopressin responses to haemorrhage in conscious rats 5,7,12 . Although we have demonstrated a link between the central renin–angiotensin (RAS) and cholinergic systems 13 suggesting that the central RAS may be involved in the pressor response to central choline, 2 changes in plasma renin activity (PRA; as an index of peripheral RAS activity) following choline administration have not been investigated in a systematic manner. In previous studies, we observed that PRA showed a tendency to decrease following intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 94%
“…In past years, considerable evidence has accumulated from experimental studies in rats showing that central administration of choline, a precursor of the neurotransmitter acetylcholine (ACh), increases blood pressure in normotensive rats 1–4 and restores blood pressure when rats are made hypotensive by acute haemorrhage, 5–7 endotoxin treatment, 8 chemical sympathectomy, 9 peripheral α‐adrenoceptor or autonomic ganglionic blockade 10 or spinal cord transection shock 11 . Elevations in plasma catecholamines and vasopressin have been shown to be associated with and involved in the pressor response to choline in either normotensive 1 or hypotensive 5,7–12 states.…”
Section: Introductionmentioning
confidence: 99%